An end-use energy analysis in a Malaysian public hospital - Saidur R.; Hasanuzzaman M.; Yogeswaran S.; Mohammed H.A.; Hossain M.S. (Elsevier Ltd, 2023)
The commercial sector consumes 8-50% of the total energy consumption for a few selected countries around the world. An energy audit was conducted in a Malaysian public hospital to identify energy using equipment and their energy consumption breakdown. Different energy saving measures have been identified and applied for electrical motors used in this hospital. It was estimated that this hospital consumed about 19,311 MW h for the year 2008. It was also estimated that about 212 MW h, 250 MW h and 317 MW h of annual energy can be saved using energy-efficient motors at 50%, 75% and 100% loads, respectively. In addition, use of variable speed drives are expected to save 1735 MW h, 4048 MW h and 6361 MW h of annual energy consumption for 20%, 40% and 60% speed reductions, respectively. It was found that the payback period for using high efficiency motors at different loads is less than a year which is economically very viable. However, the use of variable speed drives was found to be economically viable for larger motors for higher speed reductions. The study also found that a sizeable amount of emissions can be reduced for the different energy savings measures applied for electrical motors. 2010 Elsevier Ltd.